Muhibah is not religious pluralism: the understanding of religious coexistence among religious leaders in Malaysia - Ibrahim, Haslina; Rokis, Rohaiza; Wan Husin, Wan Nurhasniah (Institut Kefahaman Islam, Malaysia ( IKIM), 2016)
Muhibah is a social philosophy on pluralistic coexistence in Malaysia. It has a profound historical background that deserves to be learnt and appreciated by the Malaysian people and its leaders. Religious pluralism however, is a philosophy developed by John Hick as a response against the Christian exclusive interpretation of the doctrine of salvation. Ironically, of late, there has been a global call which persistently promotes religious pluralism as the philosophy of the day. In Malaysia, the awareness and support for religious pluralism emerged among the religious NGOs at the beginning of the 21st century. Since then, there has been been persistent propagation of religious pluralism in Malaysia. Muhibah on the other hand, remain as a blueprint on unity and national integration in the government policy. This article tries to provide a theoritical and historical comparison between the two terms to understand their meaning and historical significance. The article also shares some of a research findings on 14 religious leaders’ understanding of muhibah and religious pluralism. Their understanding is analysed and compared to gauge which of the two terms (according to them) better relates to religious coexistence in Malaysia. The article reports the research findings which record higher understanding of muhibah compared to religious pluralism. It is therefore suggested that muhibah is a better philosophy for understanding of religious coexistence in this country.